2023
DOI: 10.1186/s12967-023-04116-4
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between androgens and the immune response in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a metabolic-reproductive-endocrine disorder that, while having a genetic component, is known to have a complex multifactorial etiology. As PCOS is a diagnosis of exclusion, standardized criteria have been developed for its diagnosis. The general consensus is that hyperandrogenism is the primary feature of PCOS and is associated with an array of physiological dysfunctions; excess androgens, for example, have been correlated with cytokine hypersecretion, adipocyte proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…The evidence has shown that ROS activates proinflammatory mediators, such as NF-κB and CRP, subsequently inducing inflammation. 49 CRP has pro- and anti-inflammatory effects during inflammation, complement system activation, and infiltration-suppressing properties. In the study, the serum CRP level and IL-6 and NF-κB immunopositive cells were increased in the liver and kidney tissues of the rats treated with PAX.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence has shown that ROS activates proinflammatory mediators, such as NF-κB and CRP, subsequently inducing inflammation. 49 CRP has pro- and anti-inflammatory effects during inflammation, complement system activation, and infiltration-suppressing properties. In the study, the serum CRP level and IL-6 and NF-κB immunopositive cells were increased in the liver and kidney tissues of the rats treated with PAX.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy to eighty percent of women with PCOS have hyperandrogenism ( Baptiste et al 2010 , Huang et al 2010 ), which can have both inhibitory and stimulatory effects on immune cells. Disrupted immune responses and a state of chronic inflammation contribute to ovarian dysfunction in patients with PCOS ( Shabbir et al 2023 ). Few studies to date have investigated the effects of excess androgens on inflammation in women with PCOS.…”
Section: The Immune Systemmentioning
confidence: 99%
“…Similarly, dietary monounsaturated fatty acids improved liver insulin sensitivity by enhancing the function of M2-like Kupffer cells [ 127 ]. Likewise, M1-like macrophages also contribute to insulin resistance in the development of atherosclerosis in mice and polycystic ovary syndrome in women [ 128 , 129 ]. Thus, macrophage-mediated inflammation acts as a common factor in the pathogenesis of various metabolic diseases.…”
Section: Macrophages and Therapeutic Resistance In Metabolic Diseasesmentioning
confidence: 99%